Enhancing the thermal stability of switched domains in lithium niobate single-crystal thin films. Issue 7 (May 2020) - Zhang, Liaoyuan; Geng, Wenping; Chen, Xi; Li, Yimeng; Qiao, Xiaojun; Hou, Xiaojuan; He, Jian; Mu, Jiliang; Yang, Yuhua; Chou, Xiujian
Abstract: Lithium niobate on insulator (LNOI) is widely used in optical, acoustic, domain wall current (DWC)-based integrated circuits and other domain engineering devices, enabling higher material performance, higher domain integration density and more advanced applications. However, there are hidden dangers of thermal failure in these highly integrated domain engineering devices. Therefore, maintaining thermal stability of domain structures in ferroelectric single-crystal thin films is an important and challenging task. Here, thermally induced structure reconstruction of tailored metastable switched domains was research in a 500 nm thick congruent lithium niobate (CLN) thin film, and a method for enhancing the thermal stability of switched domains was proposed. Piezoresponse force microscopy (PFM) and a polyheater are used to accurately monitor the thermal evolution of switched domains in CLN thin film sample. The results indicate the switched domain structures determine the thermal stability, and the enhanced thermal stability of the switched domains increases from 55 to 85 °C–150 °C. In this contribution, the thermal failure in domain engineering devices can be avoided effectively. The investigation paves the way for the development of domain engineering devices based on lithium niobate (LN) thin films.